A thin film of a type II Ge clathrate epitaxially grown on a Ge substrate. Issue 30 (6th July 2016) - Kume, Tetsuji; Ban, Takayuki; Ohashi, Fumitaka; Jha, Himanshu S.; Sugiyama, Tomoya; Ogura, Takuya; Sasaki, Shigeo; Nonomura, Shuichi
Abstract : Type II Ge clathrate (Na x Ge136 ) films have been epitaxially grown on Ge(111) substrates with a relationship of Na x Ge136 (110)//Ge(110). Abstract : A thin film of a type II Ge clathrate, Na x Ge136, was epitaxially grown on a (111) substrate of Ge with a diamond structure (α-Ge). A Zintl phase NaGe film was synthesized in advance by a reaction of the substrate surface with Na vapor under an Ar atmosphere, and was highly oriented such that the NaGe(100) planes were parallel to the Ge(111) surface. The NaGe film was transformed to the Na x Ge136 film by heat treatment under dynamic vacuum. XRD measurements demonstrated that the prepared film consisting of twin crystals with a (111) twin plane was epitaxially grown with the <111> direction normal to the substrate surface. It was also suggested that the lattice mismatch between Na x Ge136 and the Ge substrate is relaxed by a buffer layer of α-Ge having a triple-period superlattice. The electrical resistivity of the Na x Ge136 film was estimated from the I – V measurements to be in the order of 10 1 –10 2 Ω m.